Association between social capital and mental health among older people living with HIV: the Sichuan Older HIV-Infected Cohort Study (SOHICS) - Jiayu Han; Peng Jia; Yuling Huang; Bo Gao; Bin Yu; Shifan Yang; Jun Yu; Jun Xiong; Chang Liu; Tian Xie; Peijie Dong; Chao Yang; et al. (BMC, 2020)
Abstract Background Mental health problems are common among older people living with HIV and associated with poorer health outcomes. Social capital is an important determinant of mental health problems but under-studied in this population. This study investigated the association between social capital and mental health problems among older people living with HIV in China. Methods The study was based on the baseline data of a cohort study investigating mental health among older people living with HIV in Sichuan, China during November 2018 to February 2019. Participants were people living with HIV aged ≥50 years living in Sichuan province. Stratified multi-stage cluster sampling was used to recruit participants from 30 communities/towns; 529 out of 556 participants being approached completed the face-to-face interview. Social capital was measured by two validated health-related social capital scales: the Individual and Family scale and the Community and Society scale. Presence of probable depression (CES-D-10 score ≥ 10) and probable anxiety (GAD-7 score ≥ 5) were used as dependent variables. Two-level logistic regression models were applied to examine the association between social capital and probable depression/anxiety. Results The prevalence of probable depression and probable anxiety was 25.9% (137/529) and 36.3% (192/529), respectively. After adjusting for significant covariates, the individual/family level of social capital was inversely associated with both probable depression (odds ratios (OR): 0.89, 95% CI: 0.84-0.93, p < 0.001) and probable anxiety (OR: 0.90, 95% CI: 0.86-0.95, p < 0.001). The community/society level social capital was associated with probable depression (OR: 0.91, 95% CI: 0.84-0.99, p < 0.001) but not probable anxiety (p > 0.05). Conclusions Interventions building up social capital should be considered to improve mental health of older people living with HIV. Some useful strategies include cognitive processing therapy, improving community networking and engagement, and promoting social bonding with neighborhood.